Safety and immunogenicity of tetravalent live-attenuated dengue vaccines in Thai adult volunteers: role of serotype concentration, ratio, and multiple doses - Sabchareon, A; Lang, J; Chanthavanich, P; Yoksan, S; Forrat, R; Attanath, P; Sirivichayakul, C; Pengsaa, K; Pojjaroen-Anant, C; Chokejindachai, W; Jagsudee, A; Saluzzo, JF; et al. (The American journal of tropical medicine and hygiene, 2002)
Dengue fever, caused by four serotypes of a mosquito-borne virus, is a growing problem in tropical countries. Currently, there is no treatment or vaccine. We evaluated safety and immunogenicity of two doses, given six months apart, of seven formulations of dengue tetravalent live-attenuated vaccine (containing different concentrations of the component viruses) versus placebo in 59 flavivirus-seronegative Thai adults. The first dose was the more reactogenic. Most volunteers experienced clinically moderate fever, headache, myalgia, eye pain or rash 7-11 days after injection, generally lasting three days or less. Modest decreases in platelets and neutrophils were observed. After one dose, 58% of dengue recipients seroconverted (neutralizing antibody level > or = 1:10) against > or = 3 serotypes; 35% seroconverted against all four. After the second dose, seroconversion was 76% and 71%, respectively. All subjects seroconverted to serotype 3 after one dose. Serotype 4 elicited the lowest primary response but the highest increase in seroconversion after the second dose.